Characteristics of Triple Negative Subtype Breast Cancer in Dr. Hasan Sadikin General Hospital for 5 Years (2019-2023): An Observational Study - Gunawan, Benny; Kiki. A. Rizki; Monty P. Soemitro; Maman Abdurahman; Yohana Azhar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Triple-negative breast cancer has a percentage of 15% to 20% in breast cancer patients at the time of first diagnosis. Guidelines from St. Gallen guidelines, the American Society of Clinical Oncology, and the American College of Pathology state that triple-negative breast cancer is breast cancer with ER and PR expression <1%. As an aggressive subtype, outcomes are poor when compared with hormone receptor-positive. Methods: This research is an observational study. The research subjects in this study were triple-negative breast cancer patients in Dr. Hasan Sadikin General Hospital, Surgical Oncology division, West Java, Indonesia, from October 2018 - November 2023. There were 702 research subjects who would be studied. Characteristics of triple-negative breast cancer were taken from medical records. Results: The results showed that the average age of the subjects was 47 years. Based on histology, the most common was Invasive Carcinoma of no special type (86.75%), followed by Invasive lobular carcinoma (7.26%), medullary carcinoma (1.7%), micropapillary carcinoma (0.99%), metaplastic carcinoma (2.36%) and the least amount is Pleomorphic invasive lobular carcinoma (0.71%). The side of the breast affected is not significant, and the highest grade is 3. The involvement of lymph node metastases is due to aggressive tumor subtypes and lymphovascular invasion. Lymphovascular invasion is known to be a negative prognostic factor. It is a late stage for metastasis and local recurrence. Conclusion: Triple-negative breast cancer is breast cancer that has histopathological heterogeneity; most of the tumors are grade 3 and have significant metastases in regional lymph nodes. There is no significant relationship between grading and regional lymph node metastases. there is a significant relationship between lymphovascular invasion and regional lymph nodes metastases.